Intercultural Awareness Levels of Indonesian Pre-service Teachers in International Teaching Practicum - Nurhastuti, Devi; Basikin, Basikin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Culture shocks, miscommunications, and even conflict will occur due to a lack of intercultural communication skills. Effective communication with native speakers requires language abilities, cultural awareness, and familiarity with local customs. Several studies on intercultural relationships have been documented. However, there is still limited research on the levels that affect intercultural awareness. This study aims to examine the intercultural awareness of pre-service teachers. This study aims to investigate the levels that affect intercultural awareness among aspiring pre-service teachers participating in an international teaching practicum (ITP). The design used a qualitative multiple-case study. Interviews with eight aspiring English pre-service teachers from Indonesia were conducted to collect data. The results show that the majority of participants agreed that during an international teaching practicum program, they gained the ability to compare and mediate cultural differences and similarities. Indonesian pre-service teachers being investigated had good intercultural awareness. The findings suggest important practical implications for providing students with sufficient references to assist pre-service teachers in enhancing and developing their intercultural teaching abilities.